Lipid Peroxidation and Antioxidant Status in Î²-Thalassemic Patients: Effect of Iron Overload - Bassm N. Aziz; Mohammad A. Al-Kataan; Wasan K. Ali (College of Pharmacy University of Baghdad, 2017)
To study the effect of iron overload due to continuous blood transfusions on peroxidation products, such as malondialdehyde (MDA) and peroxynitrite, with evaluation of some antioxidants like, glutathione (GSH), superoxide dismutase (SOD), vitamin A, vitamin C, vitamine E, Ceruloplasmin, uric acid and albumin in thalassemia patients. Forty patients with thalassemia major, aged 5 to 15 years, were carried out in Abn-Alatheer Teaching Hospital in Mosul city, during the period from October 2007 to April 2008. They were on Chelation therapy with desferÂrioxamine. They were divided into two groups, the first one without iron overload (90,97Â±12.92), and the second one with iron overload (157.75Â±7.57). All the patients were received whole blood. Blood samples were collected before and after blood transfusion. The results showed that there were significant increase in MDA and peroxynitrite in patients with iron overload five days before and after blood transfusion in compared with groups having normal iron level. On the other hand, glutathione, superoxide dismutase activity, Vitamin A, vitamin C, vitamin E, albumin and ceruloplasmin were significantly decreased whereas, uric acid was increased significantly. It is concluded that, Iron over load due to continuous blood transfusion in thalassemia causes increase in oxidative tissue damage with a changes in antioxidants status. Key Words: Beta-thalassemia, lipid peroxidation, antioxidants, Malondialdehyde, Iron